BRAZILIAN AGRIBUSINESS IN MOZAMBIQUE: THE PROSAVANA PROGRAMME CASE STUDY/ O agronegócio brasileiro em Moçambique: estudo de caso sobre o Programa ProSAVANA/ El agronegocio brasileño en Mozambique: estudio de caso sobre el Programa ProSAVANA - Kobashikawa, Tamy Yukie (2020)
This paper is about the ProSAVANA Programme, a trilateral cooperation project between Japan, Brazil and, Mozambique. ProSAVANA Programme goal is to develop the agriculture sector in the Nacala Corridor and it has been controversial due to conflicts among government, private corporations, and civil society organizations. Private investments were expected to occur in the Nacala Corridor, mainly from Brazilian agribusiness, however, Brazilian private investments in Mozambique’s agriculture sector have been in a stagnant state in the period 2007-2017.The paper examines the status of the ProSAVANA Programme and what are the difficulties to Brazilian agribusiness invest to Mozambique. Current challenges of the programme were found as follows: (1) high risk of investment due to non-existent public subsidies to small, medium and large-scale agribusiness; (2) “land property” law bureaucracy; and (3) civil society mobilization against ProSAVANA. All they are key factors to repel Brazilian agribusinesses. Como citar este artigo:KOBASHIKAWA, Tamy Yukie. Brazilian agribusiness in Mozambique: the ProSAVANA Programme case study. Revista NERA, v. 23, n. 51, p. 345-365, jan.-abr., 2020.